Fruit pomace as a source of alternative fibers and cellulose nanofiber as reinforcement agent to create molded pulp packaging boards. (August 2017) - Gouw, Virginia P.; Jung, Jooyeoun; Simonsen, John; Zhao, Yanyun
Abstract: Fruit pomace (FP) as a source of fiber partially replaced recycled newspaper (NP) to create molded pulp boards (FPBs). Blueberry (BP), cranberry (CP), and apple pomace (AP) with different fiber compositions and morphologies were studied for their compatibility with NP. Cellulose nanofiber (CNF) was used to improve adhesion between FP and NP. FP/NP ratio and CNF concentration were optimized via central composite design to create FPBs with lower water absorption, and similar flexural strength and strain to 100% newspaper board (NPB). Lignocellulosic composition and fiber morphology of FP affected its compatibility with NP. Incorporating CNF reduced water absorption and increased flexural strength and strain of FPBs, but the amount of required CNF varied among the types of pomace. This study demonstrated that FP can partially substitute NP to create FPBs with better or similar properties to 100% NPB.